2008
DOI: 10.1109/tuffc.2008.715
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of MR-temperature mapping of ultrasonic heating from a CMUT

Abstract: In the last decade, high intensity focused ultrasound (HIFU) has gained popularity as a minimallyinvasive and non-invasive therapeutic tool for treatment of cancers, arrhythmias, and other medical conditions. HIFU therapy is often guided by magnetic resonance imaging (MRI), which provides anatomical images for therapeutic device placement, temperature maps for treatment guidance, and post-operative evaluation of the region of interest. While piezoelectric transducers are dominantly used for MR-guided HIFU, cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Consequently, a correction term is used to make the model more accurate. 1 Missing √ 5/3 factor in Ftot of Ref. [3] is corrected here.…”
Section: Modelling Nonlinear Components In Spicementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a correction term is used to make the model more accurate. 1 Missing √ 5/3 factor in Ftot of Ref. [3] is corrected here.…”
Section: Modelling Nonlinear Components In Spicementioning
confidence: 99%
“…HIFU tools have been in use for the last 50 years, and since the introduction of the technology, piezoelectric transducers have been the core element of the device. Recently, it has been demonstrated that CMUTs are strong competitors and can be used as a HIFU transducer [1]. As CMUTs are fabricated using silicon micromachining techniques, it is possible to design a CMUT that operates at a specific frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ease of micro-fabricating transducer arrays in various shapes and configurations, CMUTs are used in various emerging applications such as medical ultrasound imaging (Demirci et al 2004;Caliano et al 2005;Knight 2002;Cianci et al 2004;Chang et al 2006), detection and treatment of cancer (by using high intensity ultrasound waves) ), blood flow measurements (Wang et al 2007), non-destructive evaluation (NDE) (Octavio et al 2007), ultrasonic heating (Wong et al 2008), chemical or biological micro sensor (Lee et al 2008;Ramanaviciene et al 2010), power transmission (Bayram et al 2005), and therapeutic ultrasound (Wong et al 2006(Wong et al , 2010. The performance requirements and challenges that need to be overcome vary significantly among these applications, and they all require specific design efforts, even though they essentially use the same transducer technology.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction c apacitive micromachined ultrasonic transducers (cMUTs) [1], [2] have been of interest because of their wider bandwidth compared with piezoelectric transducers [3]. Medical imaging [4]- [6], high-intensity focused ultrasound (HIFU) treatment [7], [8], and intravascular ultrasound (IVUs) [9]- [11] are just a few of the application areas where they are currently being considered as a promising technology.…”
mentioning
confidence: 99%